2017
DOI: 10.1371/journal.pone.0176289
|View full text |Cite
|
Sign up to set email alerts
|

Comparing bee species responses to chemical mixtures: Common response patterns?

Abstract: Pollinators in agricultural landscapes can be exposed to mixtures of pesticides and environmental pollutants. Existing mixture toxicity modelling approaches, such as the models of concentration addition and independent action and the mechanistic DEBtox framework have been previously shown as valuable tools for understanding and ultimately predicting joint toxicity. Here we apply these mixture models to investigate the potential to interpret the effects of semi-chronic binary mixture exposure for three bee spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
53
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 40 publications
6
53
1
Order By: Relevance
“…We therefore agree with Heard et al (2017) that A. mellifera is a sufficient 258 proxy for wild bee species in laboratory acute mortality testing [17]. However, it is still 259 necessary to investigate less well-known issues such as effects of pesticides mixtures [32,33], prolonged pesticides exposure [17] or effects of pesticide adjuvants [34]. 261 An assessment factor of 10 proved to be protective for O. bicornis when applied honey 262 bee endpoints for nearly all tested insecticides.…”
supporting
confidence: 52%
See 1 more Smart Citation
“…We therefore agree with Heard et al (2017) that A. mellifera is a sufficient 258 proxy for wild bee species in laboratory acute mortality testing [17]. However, it is still 259 necessary to investigate less well-known issues such as effects of pesticides mixtures [32,33], prolonged pesticides exposure [17] or effects of pesticide adjuvants [34]. 261 An assessment factor of 10 proved to be protective for O. bicornis when applied honey 262 bee endpoints for nearly all tested insecticides.…”
supporting
confidence: 52%
“…However, wild bee species (i.e. bumble bees, solitary bees) may show 32 quite different responses to pesticide exposure due to differences in physiology and 33 ecology [14]. As a reaction to the information scarcity regarding the sensitivity of 34 bumble bees and solitary bees, the European Food Safety Authority (EFSA) proposed 35 the inclusion of the buff-tailed bumblebee Bombus terrestris and the red mason bee…”
mentioning
confidence: 99%
“…Comparison of species is, however, not the only important application of the AmP website. Prediction of effects of global change [ 5 ], understanding the geographic distribution of species [ 6 8 ], the effects of (toxic) chemical compounds [ 9 12 ], the optimization of bio-production (e.g. aquaculture and agriculture [ 13 15 ]), stock management, the best re-introduction of endangered species or the control of invading species [ 16 ], are just examples of applications where detailed knowledge of energetics of species in a DEB context is very useful.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that inhibiting P450 activity can greatly increase toxicity of several pyrethroids ( Johnson et al 2006 , 2012 ) and neonicotinoid insecticides ( Iwasa et al 2004 , Manjon et al 2018 ) to honey bees. The ergosterol biosynthesis inhibitor (EBI) fungicides are known to suppress P450 activity ( Hassold et al 2009 ), and the presence of some EBI fungicides can also enhance neonicotinoids toxicity to honey bees ( Sgolastra et al 2017 , Robinson et al 2017 , Tsvetkov et al 2017 ).…”
Section: Discussionmentioning
confidence: 99%